2016
DOI: 10.5194/acp-2016-614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radical chemistry at a rural site (Wangdu) in the North China Plain: Observation and model calculations of OH, HO<sub>2</sub> and RO<sub>2</sub> radicals

Abstract: A comprehensive field campaign was carried out in summer 2014 in Wangdu located in the North China Plain. A month of continuous OH, HO 2 and RO 2 measurements were achieved.Observations of radicals by laser induced fluorescence (LIF) technique gave daily maximum concentrations between (5-15)×10 6 cm −3 , (3-14)×10 8 cm −3 and (3-15)×10 8 cm −3 for OH, HO 2 and RO 2 , respectively. Measured OH reactivities (inverse OH lifetimes) were 10 to 20 s −1 during day-5 time. A chemical box model constrained by trace-gas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(47 citation statements)
references
References 35 publications
(71 reference statements)
4
42
1
Order By: Relevance
“…In contrast to some of the earlier HO2 model-measurement comparisons which diverged at NO concentrations > 1ppbv with models increasingly under-predicting the levels of HO2 observed, the predicted levels of HO2 were in good agreement with HO2 observations made in Wangdu over the whole range (0.1 -4 ppbv) of NO encountered (Tan et al, 2017). However, the authors did report an increasing model under-prediction of the observed 10 RO2 with increasing NO (Tan et al, 2017).…”
Section: Introductioncontrasting
confidence: 46%
See 4 more Smart Citations
“…In contrast to some of the earlier HO2 model-measurement comparisons which diverged at NO concentrations > 1ppbv with models increasingly under-predicting the levels of HO2 observed, the predicted levels of HO2 were in good agreement with HO2 observations made in Wangdu over the whole range (0.1 -4 ppbv) of NO encountered (Tan et al, 2017). However, the authors did report an increasing model under-prediction of the observed 10 RO2 with increasing NO (Tan et al, 2017).…”
Section: Introductioncontrasting
confidence: 46%
“…The same assumption was drawn in the recent ROx study in Wangdu, China (Tan et al, 2017). This assumption means that the 25 concentration of RO2 observed may be a lower estimate.…”
Section: Rox-lif Descriptionmentioning
confidence: 87%
See 3 more Smart Citations